IRTKS is correlated with progression and survival time of patients with gastric cancer. Issue 8 (24th June 2017) - Huang, Li-Yu; Wang, Xuefei; Cui, Xiao-Fang; Li, He; Zhao, Junjie; Wu, Chong-Chao; Min, Lingqiang; Zhou, Zhicheng; Wan, Lixin; Wang, Yu-Ping; Zhang, Chao; Gao, Wei-Qiang; et al.
Abstract : Background and objectives: IRTKS functions as a novel regulator of tumour suppressor p53; however, the role of IRTKS in pathogenesis of gastric cancer is unclear. Design: We used immunohistochemistry to detect IRTKS levels in 527 human gastric cancer specimens. We generated both IRTKS -deficient and p53 -deficient mice to observe survival time of these mice and to isolate mouse embryonic fibroblasts (MEFs) for evaluating in vivo tumorigenicity. Co-immunoprecipitation was used to study the interaction among p53, MDM2 and IRTKS, as well as the ubiquitination of p53. Results: IRTKS was significantly overexpressed in human gastric cancer, which was conversely associated with wild-type p53 expression. Among patients with wild-type p53 (n=206), those with high IRTKS expression (n=141) had a shorter survival time than those with low IRTKS (n=65) (p=0.0153). Heterozygous p53 +/− mice with IRTKS deficiency exhibited significantly delayed tumorigenesis and an extended tumour-free survival time. p53 +/− MEFs without IRTKS exhibited attenuated in vivo tumorigenicity. IRTKS depletion upregulated p53 and its target genes, such as BAX and p21 . Intriguingly, IRTKS overexpression promoted p53 ubiquitination and degradation in MEFs and gastric cancer cells. Under DNA damage conditions, IRTKS was phosphorylated at Ser331 by the activated Chk2 kinase and then dissociated from p53, along with the p53-specific E3 ubiquitin ligase MDM2, resulting in attenuated p53 ubiquitination and degradation. Conclusion: IRTKS overexpression is negatively correlated with progression and overall survival time of patients with gastric cancer with wild-type p53 through promotion of p53 degradation via the ubiquitin/proteasome pathway.